Notes on the language of Northern Russian lamentations. 2. Composite nominations, their structure and semantics - Tolstaya, Svetlana M. (Slověne, 2020)
The paper is devoted to the language of the Northern Russian lamentations collected and published by E.V. Barsov 150 years ago. The author uses the material of wedding lamentations to study the typical folklore language — composite nominations, i.e. nouns, verbs, and other parts of speech formed on the basis of two (rarely three) lexical units: 1) integral compound words (svet-batiushka, drug-podruzhka, zvon-unylyj), 2) phrases with an application (dusha-devushka, doch’-nevol’nica, idti-shatat’s’a), 3) tautological phrases, i.e. complete or partial reduplications (vol’a-vol’ushka, mesto-mestechko, um-razum, gnevev-gneven) or combinations of synonyms (put’-dorozhen’ka, rod-plem’a, znat’-vedat’, gl’adet’-smotret’, strogo-grozno, zhalko-unylo), 4) constructions with a compositional relationship (gusi-lebedi, zlato-serebro, khleb-sol’, kormit’-poit’, dosyta-dop’ana). The classification is based on the following characteristics: structure (the declination of the components of the phrases), macro-syntax (coordination with both members of the binomial or one of them), micro-syntax (relationship of the components with each other—the subordination or composition) and semantics (whether members of the phrase semantically independent, or one of the members serves as an emotional, evaluative, functional definition, addition, refinement, modification of the other). The specifics of folklore material, and particularly of poetic texts of Northern Russian wedding lamentations, are their structural and syntactic diffuseness, blurring of borders between different types of composite units, the tendency to free syntax of the paratactic type, avoiding explicit means of expressing semantic relations (especially subordinates), the predominance of composition over subordination not only in sentences, but also between components of phrases.